Estimation of nitric oxide and malondialdehyde in serum and saliva of patients with oral lichen planus - V P Jayasekharan; R Ramya; K Rajkumar; T Dinesh Kumar; G Nandhini; S Satish Kumar (SRM Journal of Research in Dental Sciences, 2014)
Aim: The aim of this study is to evaluate the levels of malondialdehyde (MDA) and nitric oxide (NO) in serum and saliva of patients with oral lichen planus (OLP) and to compare the levels. Materials and Methods: The study included 10 cases of OLP patients which formed the study group and 10 cases of healthy individuals, which formed the controls. The saliva sample was diluted with 10 ml of phosphate buffered saline in order to neutralize the pH. After diluting, the mixture was centrifuged for 5 min at 3000 rpm and the supernatant fluid was stored at −80°C until use. Blood was allowed to clot and was centrifuged for 5 min at 3000 rpm. The clear serum was separated and stored at −80°C until analysis. Statistical Analysis: The analysis was done using SPSS software. Mean and standard deviations were analyzed using the independent samples t-test to compare the mean values of NO and MDA assay. Results: The levels of NO and MDA were significantly higher in serum and saliva of cases with lichen planus than in normal and increase in level of NO was significantly higher than the increase in the level of MDA. Conclusion: Salivary levels of NO and MDA were found to be significantly higher than serum levels, which suggested that saliva can be used as an alternate and effective diagnostic tool in evaluating the oxidative stress status of an individual and antioxidants may be used to reverse the oxidative stress status in lichen planus.